KEMAMPUAN MENULIS PESAN SINGKAT SISWA KELAS VII SMP NEGERI SOREK DUA KABUPATEN PELALAWAN - Alfandi, Juru; Razak, Abdul; Rahman, Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study investigated the ability to write a short message class VII student of SMPN Sorek Dua Pelalawan. This study aims to determine the ability to write a short message class VII student of SMPN Sorek Dua Pelalawan This study is a descriptive-quantitative. This research data is data result of taking the test, the ability to write a short message class VII student of SMPN Sorek Dua Pelalawan. Instruments in this research is a form of an essay test on the ability to write a short message Students in grade VII SMP Negeri Sorek Dua Pelalawan. The data collection was done by using the test. The population in this study were 98 students with the determination of the full sample as many as 98 students. Data were analyzed with descriptive methods. The validity of the data obtained through the method of data validation. Results of this study of the test results the ability to write a short message Students in grade VII SMP Negeri Sorek Dua Pelalawan. Judging from the ability to write a short message seventh grade students of SMP Negeri Sorek Dua Pelalawan fall into the medium category with an average value of 79.10.Key Words: Short Message.